ENDOPHYTES FROM THE AQUATIC PLANT NELUMBO NUCIFERA: DIVERSITY PROFILE AND ACTIVITY CHARACTERIZATION - Ijarwal, Tanuja; Sharma, Bharti; Khan, Faiza; Ibeyaima, A.; Dwivedi, Anuj; Saini, Narendra; Sarethy, Indira P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Endophytes represent a niche habitat for the study of novel bio-and chemo diversity. Nelumbo nucifera is an aquatic plant that has not been characterized for endophyte diversity. This study was undertaken with the objective of isolating endophytes from submerged and aerial part of N. nucifera, study the diversity profile of the isolated endophytes and their antimicrobial, antioxidant, and siderophore production capacity. Methods: Endophytes were isolated from aerial and submerged parts of N. nucifera on different media (Starch Casein Nitrate, Glucose Yeast Extract, Nutrient and Potato Dextrose agar). These were further characterized for morphology (colony characteristics, Gram reaction), physiological characteristics (carbon, nitrogen utilization) and activity (antimicrobial, antioxidant, siderophore production). After dereplication, twelve isolates were studied further. Results: All endophyte isolates were Gram-positive bacteria, and one was a fungus. Isolate L-300 showed the highest antioxidant capacity (238 AAE g FW-1) and L-201 least (10 AAE g FW-1. Antimicrobial activity was exhibited against bacteria and fungal targets, with 50% endophytes active against both bacteria and fungi. Isolates L-003 and L-207 exhibited activity against Gram-negative clinical isolates as also fungi. Siderophore production was shown by 58% isolates with L-208 showing maximum activity. Conclusion: This is the first report on profiling of endophytes from N. nucifera. Results show that aquatic plants harbor diverse microbial population. Many promising isolates (such as L-003, L-211, L-214 and L-300) have been characterized in this study and results obtained of antioxidant, antimicrobial and siderophore production capacity demonstrate further utility in polypharmacological studies for identifying compounds of pharmaceutical and other industrial interest. Â 